Narcissism and subjective well-being : proposed mediation model in a Singaporean sample - Diana (2011)
Self-esteem has often been considered as a mediator in the relationship between narcissism and subjective well-being (SWB). However, the significance of self-esteem is not the same across cultures with individualistic cultures consistently reporting higher self-esteem than collectivistic cultures. An alternative construct is required for a more accurate study of narcissism and SWB in non-Western countries. This study proposes self-construal as an alternative mediator to self-esteem as its effect across culture. Participants were 199 Singaporean undergraduates. The investigation involved mediation analyses using multiple regression and the Sobel Test. Results showed that self-esteem and independent self-construal to be significant mediators between narcissism and SWB. Findings from this study highlighted the challenge in studying the relationship between narcissism and SWB cross-culturally.